2016
DOI: 10.1080/14760584.2016.1218762
|View full text |Cite
|
Sign up to set email alerts
|

Advances and challenges: dendritic cell vaccination strategies for glioblastoma

Abstract: Introduction Glioblastoma is the most common primary brain tumor in adults and prognosis remains poor with a median survival of approximately 15–17 months. This review provides an overview of recent advances in the field of glioblastoma immunotherapy. Areas covered Recent advances in dendritic cell vaccination immunotherapy are showing encouraging results in clinical trials and promise to extend patient survival. In this report we discuss current scientific knowledge regarding dendritic cell (DC) vaccines, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 99 publications
0
35
0
Order By: Relevance
“…Evasion of the immune system constitutes one of the hallmarks of cancer . Cancer cells can escape immunological destruction by virtue of complex mechanisms, such as low immunogenicity, antigenic modulation, and immune suppression . Encouraging results using immunotherapies in melanoma and other cancers have demonstrated the staggering potential of redirecting the immune system, and research groups have strived toward incorporating immunotherapy into the armamentarium against HGG .…”
Section: Immunotherapeutic and Immunomodulatory Agents In Phggmentioning
confidence: 99%
See 1 more Smart Citation
“…Evasion of the immune system constitutes one of the hallmarks of cancer . Cancer cells can escape immunological destruction by virtue of complex mechanisms, such as low immunogenicity, antigenic modulation, and immune suppression . Encouraging results using immunotherapies in melanoma and other cancers have demonstrated the staggering potential of redirecting the immune system, and research groups have strived toward incorporating immunotherapy into the armamentarium against HGG .…”
Section: Immunotherapeutic and Immunomodulatory Agents In Phggmentioning
confidence: 99%
“…DCs constitute a link between the innate and adaptive immune responses and have been called the “sentinels” of the innate immune system because they look out for foreign antigens, particularly pathogen‐associated molecules. Then they take up, process, and present these antigens on MHC molecules to T and B lymphocytes . By doing so, they can trigger an adaptive immune response against those antigens .…”
Section: Immunotherapeutic and Immunomodulatory Agents In Phggmentioning
confidence: 99%
“…The idea of HCMV in GBM has led to potential immunotherapy targets for treatment of GBM. [73,74] A study conducted by Nair et al [75] evaluated whether T cells stimulated by HCMV pp65 RNA-transfected dendritic cells target and eliminate GBM tumor cells. The authors of this study concluded that HCMVspecific T cells can effectively target GBM tumor cells and their results support the rationale for the development of HCMV-directed immunotherapy in patients with GBM.…”
Section: Therapeutic Targets For Hcmvmentioning
confidence: 99%
“…[75] As a result of this association and the potential therapeutic options, several groups are exploring novel approaches to developing GBMdirected immunotherapy and vaccines. [74] Potential HCMV proteins that are being investigated for the development of immunotherapy targets include immediate early 1 (IE1), phosphoprotein 65 (pp65), and glycoprotein B (gB). [74] …”
Section: Therapeutic Targets For Hcmvmentioning
confidence: 99%
See 1 more Smart Citation